Pengaruh Beberapa Dosis Pupuk Dan Beberapa Media Tumbuh Terhadap Pertumbuhan Bibit Jabon (Anthocephalus Cadamba) - Sondri Kurniawan; Afif Bintoro; Melya Riniarti (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
Jabon wood (Anthocephalus cadamba) is a fast growing species. Currently, jabon wood is play an important rile for timber industry, included plywood, lamina, and the other timber industry. To improve the quality of wood jabon, necessary for the addition of fertilizer and improved media. Application of multiple doses of fertilizers with several media compositions was expected could increase the growth of jabon wood seedling. This observation aimed to know the effect and interaction of media composition and fertilizer on the growth of jabon wood seedling. The observation was conducted in greenhouse of Agriculture Faculty, Lampung University for 4 months. The observation was compiled factorially (3x4) in a completely randomized design (CRD) with 3 replications. The first factor was the composition of the soil medium consisting of red-yellow podzolic (100%); red-yellow podzolic + sand (1:1); red-yellow podzolic + rice husk (1:1), while the second factor was the dose of fertilizer consists of 0 g, 0.5 g , 1 g, and 1.5 g. The observed variables are added height, diameter, number of leaves, root length, and total dry weight. The results showed that media composition significantly affected, diameter, number of leaves and total dry weight. Fertilizer did not significantly affected height increment, diameter, number of leaves, root length, and total dry weight, there was no interaction between several media compositions with fertilizer. The best treatment to all growth parameters was red-yellow podzolic soil + sand (1:1) with all fertilizer doses. Keywords: fertilizer, jabon wood, podzolic,red-yellow, rice husk